Effects of Environmental Change on Travelers’ Sleep Health: Identifying Risk and Protective Factors - Xiong, Wei; Fan, Fang; Qi, Haiying (Frontiers in Psychology, 2020)
Objective The aim of this study is to predict the risk and protective factors for the differential effects of the environment on travelers’ sleep health. Methods A sample of 505 travelers who stayed overnight in one of 28 hotels completed a sleep quality scale (SQS), a reduced scale of the Morningness/Eveningness questionnaire (rMEQ), and a hotel customer satisfaction questionnaire (H-SCI). Results Individuals who are of morning type (p = 0.002), have reduced sleep duration (p = 0.010), and have high sensitivity to the sleep environment (p = 0.000) are most affected by environmental change. Interestingly, business travelers are more affected by sleep disturbances than leisure travelers, travelers who are more satisfied with hotels are less likely to experience insomnia in a new sleep environment (p = 0.000), and insomniacs are more likely to recover from insomnia during a trip (p = 0.000). Conclusion Environmental change has an inconsistent impact on the sleep health of different individuals. In a new sleep environment, the possible risk factors for sleep health include (1) being of morning type, (2) reduced sleep duration during trip, (3) sensitivity to the sleep environment, and (4) business stress, while a possible protective factor is satisfaction with the hotel. Possible factors aiding in recovery from home insomnia include (1) being of evening type and (2) higher satisfaction with the hotel.